Premenstrual syndrome and dysmenorrhea successfully managed with the Japanese traditional medicine tokito: A case report and literature review. Issue 1 (20th December 2021) - Fukai‐Watabe, Shiho; Ishibashi, Satoru; Watabe, Tokumu; Watabe, Hirotsugu
Abstract: Case: A 46‐year‐old woman suffered from decades‐long premenstrual constipation, abdominal bloating and cramping pain along with dysmenorrhea. The abdominal pain before and during menstruation was resistant to nonsteroidal anti‐inflammatory drugs. Outcome: The abovementioned symptoms were concurrently resolved with a single Kampo formula, tokito, without side effects. Tokito contains 10 herbs including anti‐spasmodic, vasodilating and analgesic agents which may contribute to the beneficial‐pleiotropic effects on premenstrual syndrome (PMS) symptoms and dysmenorrhea bothering women before and during menstruation. Conclusion: Tokito may become a viable option for treating or preventing PMS symptoms and dysmenorrhea.